1993
DOI: 10.1021/bp00021a012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of the γ‐Glutamyltranspeptidase Gene from a Pseudomonas Strain

Abstract: gamma-Glutamyltranspeptidase (GGT) was purified from a Pseudomonas sp. strain A14. The purified enzyme was found to be composed of two nonidentical subunits with molecular weights of 39,000 and 22,000 and had a pI of > 8.6. The partial N-terminal amino acid sequences of both subunits and some proteolytic fragments were determined. Using mixed oligonucleotides designed from the partial amino acid sequences as hybridization probes, one cosmid clone which contained the GGT gene was isolated from a Pseudomonas sp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…PGA was prepared from the culture in M medium of Bacillus subtilis TAM-4 by the method previously described.! 7) Bacterial strain and clilture conditions. B. subtilis TAM-4, isolated previously from soiL I 7) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PGA was prepared from the culture in M medium of Bacillus subtilis TAM-4 by the method previously described.! 7) Bacterial strain and clilture conditions. B. subtilis TAM-4, isolated previously from soiL I 7) was used.…”
Section: Methodsmentioning
confidence: 99%
“…3) However, it has been reported that GGT is involved in the reclamation of circulating glutathione in conjunction with cysteinyl-glycine dipeptidase. 4 ) On the other hand, GGTs have also been purified from Gram-negativeS 7) and positive 8 . 9 ) bacteria.…”
mentioning
confidence: 99%
“…However, GGT expression and activity in bacteria has been poorly characterized. Recently, the ggt gene for H. pylori was identified and sequenced by Chevalier et al (7), making it one of only several bacterial species in which the ggt gene has been characterized (18,34,38). Chevalier et al reported that deletion of GGT had no deleterious effect on the ability of H. pylori to grow in culture, but GGT is essential for H. pylori infection of the mouse (7).…”
mentioning
confidence: 99%
“…The physiological significance of the enzyme is largely unknown, but it is the only protease known to cleave intact glutathione, and it has been used as a clinical marker of liver damage and hepatocarcinogenesis (5,7,9). GGT-encoding genes from mammalian and bacterial species have been sequenced (3,8,12,14,17,27). The proteins have extensive homology and are translated as propolypeptides of approximately 580 amino acids which are subsequently processed to form the two subunits of the mature enzymes.…”
mentioning
confidence: 99%